Sex related differences in the characteristics and outcomes of heart failure: A sub analysis of heart failure disease management study - Grupper, Avishay; Freimark, Dov; Murad, Havi; Olmer, Liraz; Benderly, Michal; Ziv, Arnona; Friedman, Nurit; Kaufman, Galit; Silber, Haim; Kalter-Leibovici, Ofra (Frontiers in Cardiovascular Medicine, 2022)
Aims: This is a sub-analysis of a randomized controlled trial on heart failure (HF) disease management (DM) in which HF patients (N=1,360; 27.5% women) were randomly assigned to DM (N=682) or usual care (UC) (N=678). Study intervention did not significantly affect the rate of hospital admissions or mortality. This study evaluates sex-related differences in baseline characteristics, clinical manifestations, adherence to treatment and outcomes among the study cohort. Methods: Association between sex and hospital admissions and mortality was tested in multivariable models adjusted for the patients’ baseline characteristics. The primary composite outcome of the study included time to first HF hospitalization or all-cause mortality. Secondary composite outcome included number of hospital admissions and days of hospitalization, for HF and all other causes. Results: Compared to males, females recruited in the study were on average 3 years older, with higher prevalence of preserved left ventricular function (LVEF>50%) and lower frequency of ischemic heart disease (p≤0.001). Females had shorter 6-minute walking distance and worse quality of life and depression scores at baseline (p<0.001). The proportion of patients receiving HF recommended medical treatment was similar among females and males. During a median follow-up of 2.7 years (range: 0-5), there were no significant differences between females and males with respect to the time elapsed until the study primary endpoint and its components in univariate analysis (557 (56.5%) males and 218 (58.3%) females were hospitalized for HF or died for any cause; p>0.05). Multivariable analysis showed that females were significantly less likely than males to experience the primary outcome [adjusted hazard ratio [(HR)=0.835, 95% CI: 0.699, 0.998)] or to die from any cause [adjusted HR=0.712; 95%CI: 0.560, 0.901]. The sex-related mortality differences were especially significant among patients with non-preserved EF, with ischemic heart disease or with recent HF hospitalization. Females also had lower rates of all-cause hospital admissions [adjusted rate ratio=0.798; 95%CI: 0.705, 0.904] and were more likely to adhere to HF medical therapy compared to males. Conclusions: Females with HF fare better than men. Sex related differences were not explained by baseline and morbidity-related characteristics or adherence to medical treatment.